Importancia de la gestión escolar en la protección del entorno natural en la escuela “Juan León Mera”, parroquia Mulaló, del cantón Latacunga, en el periodo lectivo 2014-2015 - Guamán Reisancho, Tania Jimena (2015)
This research project has the purpose to design a strategy workshop school management allowing protection of the natural environment promoting integrated development in students. It born as an answer to the problem ¿How the lack of school management affects the protection of the natural environment at school Juan León Mera, Mulaló parish, Canton Latacunga, for school year 2014-2015? The methodology used is descriptive, not experimental, field, analytical and bibliographic; descriptive to characterize the problem; no experimental identification without altering phenomenon; field to obtain information from the manager, teachers, students and parents; Analytical for the realization of analysis and interpretation of research results; bibliographic history for the research. The results obtained we demonstrate a lack of teachers in the correct application of school management. The stages of school management they are not applied correctly, prevent manage institutional projects generating activities that help environmental education and the care and protection of the natural environment. The contributions were the design and school management workshops and environmental protection application.